Walls within the walls the architecture of Intramuros by the end of the Spanish regime - Arcilla, John Paul Escandor (Quezon City: Asian Center, University of the Philippines Diliman, 2021)
Intramuros in Manila is the only locality in the Philippines where all development is regulated by national law purely for cultural and historical reasons. Effective regulations have been in existence in Intramuros since 1979 when Presidential Decree No. 1616 was put into effect, setting the Spanish-era colonial style, specifically the architecture of Manila in the 1890s, as the only aesthetic allowable in the district. Curiously however, despite four decades of sweeping architectural regulations, the Intramuros Administration was able to operate and implement the concept of the "Spanish-era colonial style," specifically the style of the 1890s, even with the absence of a comprehensive source material on the subject or a codified architectural style manual. This thesis aims to aid in resolving this gap.

In order for this to be achieved, the main goal of this thesis was to create a narrative on the architecture of Intramuros at the end of the Spanish regime. This thesis was able to achieve this goal by (a) laying out a meaningful discussion based on a socio-political framework [of] the architecture of Intramuros at the end of the Spanish regime in 1898, by (b) creating a discussion on how the Church and State, the main power players during the era, reflected their authority through physical fabric, and by (c) nuancing how the architecture of non-state/church actors, the Walled City's population, responded in kind to the architecture of the Church and State.

Using archival data and following a socio-political framework around the relationship of politics and architecture, the following were found (1) the architecture of Intramuros by the end of the Spanish colonial regime is vernacular, as represented by the Bahay na Bato, and cosmopolitan, as represented by the Non-Bahay na Bato type, (2) the Bahay na Bato type had universal appeal, (3) the architecture of the period a product of the local geography as well as the accretion hundreds of years of socio-political history, (4) structures of the state-church hegemony versus the structures of the non-state/church where differenced by size and style, (5) the Church and State in Intramuros projected power through monumental architecture and were mostly European in style, as represented by Non-Bahay na Bato types, and finally (6) The architecture of the people were comparatively smaller in scale and were mostly vernacular, as represented by the Non-Bahay na Bato type/.
Includes bibliographical references.
Thesis (Master of Arts in Philippine Studies)
Keywords: Intramuros (Manila, Philippines) -- History; Intramuros (Manila, Philippines) -- Politics and government